Book Review: Sumatra. Geology, Resources and Tectonic Evolution - Fatrial Bahesti (Berita Sedimentologi, 2011)
BARBER, A. J., CROW, M. J. and MILSOM, J. S. 2005. Sumatra. Geology, Resources and Tectonic Evolution. Geological Society Memoir no. 31. ix + 290 pp. London, Bath: Geological Society of London. ISBN 1 86239 180 7. doi:10.1017/S0016756806212974.